Pengaruh Wisata Desa Adat Osing Terhadap Peningkatan Pendapatan Keluarga Masyarakat Kemiren Banyuwangi - Estu Handayani; Tintin Harlina (RELASI : JURNAL EKONOMI, 2021)
The development of tourism in Banyuwangi has a very significant effect on improving the economy of the community, especially in the village of Kemiren. With the increasing number of tourist visits to the Osing traditional village, it will also affect the increase in the family income of the Kemiren village community. The economic influence due to tourism cannot always be enjoyed by all levels of society who live in the tourist area, sometimes there are components that do not enjoy it either individually or in groups. From this background an analysis was carried out on "The Influence of Osing Traditional Village Tourism on Increasing Family Income of the Kemiren Banyuwangi Community". The purpose of this study was to determine the effect of the number of tourists, infrastructure, and accommodation on increasing the income of the Kemiren village community. The method used in this research is quantitative descriptive analysis and regression analysis using SPSS Statistic 23. The results of this study indicate that the number of tourists, infrastructure and accommodation have a positive and significant effect on family income. It is proven by the variable availability of independence which makes it attractive for tourists to visit the traditional village of Kemiren, thereby increasing the family income of the Kemiren village community. And these results prove that the impact of tourism can be enjoyed as a whole by the people of Kemiren village. Keywords: Kemiren Village, number of tourists, infrastructure, accommodation, family income